Nitrogen Adsorption Studies on Non-Porous Silica: The Annealing Effect over Surface Non-Bridging Oxygen Atoms - Carmelo Herdes; Patrícia A. Russo; M. Manuela L. Ribeiro Carrott; Peter J.M. Carrott (Adsorption Science & Technology)
This contribution compares experimental nitrogen adsorption isotherms with molecular simulation results on effective non-porous silica models. A Molecular Dynamic (MD) annealing temperature scheme was adopted for the formulation of three samples of the solid surface. By means of Grand Canonical Monte Carlo (GCMC) simulations, nitrogen adsorption isotherms were obtained for each sample, with charged and uncharged nitrogen molecules, and compared with relevant experimental data. Following comparison of the experimental and simulated nitrogen results, a tuning process over the energetic parameter of the oxygen atoms was performed for the final proposed model. Specifically, the results are presented in terms of adsorption isotherms with an emphasis on the annealing effect over relevant model parameters, such as the surface concentration and the distribution of non-bridging oxygen atoms.